2012
DOI: 10.4238/2012.september.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of CTX-M-14 extended-spectrum β-lactamase and plasmid-mediated ACT-like AmpC β-lactamase produced by Klebsiella pneumoniae isolates from chickens in Henan Province, China

Abstract: ABSTRACT. Extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases produced by a clinical isolate of Klebsiella pneumoniae from chickens were detected with confirmatory phenotypic tests of the Clinical and Laboratory Standards Institute. The minimum inhibitory concentrations of 18 antibacterial drugs against K. pneumoniae were determined by the 2-fold microdilution method. The genotype and subtype of the ESBL-producing and AmpC β-lactamase-producing K. pneumoniae isolate were identified by PCR amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…The susceptibility profile of K. pneumoniae strains revealed a high resistance to ampicillin, nalidixic acid, sulphonamides and tetracycline. These data corroborate the findings reported by Kim et al (2005) and Wu et al (2012), who demonstrated high levels of resistance to beta-lactams and tetracyclines. The results of the present study showed that 25% of the strains possessed multiple resistance (to three or more classes of antimicrobials).…”
Section: Discussionsupporting
confidence: 91%
“…The susceptibility profile of K. pneumoniae strains revealed a high resistance to ampicillin, nalidixic acid, sulphonamides and tetracycline. These data corroborate the findings reported by Kim et al (2005) and Wu et al (2012), who demonstrated high levels of resistance to beta-lactams and tetracyclines. The results of the present study showed that 25% of the strains possessed multiple resistance (to three or more classes of antimicrobials).…”
Section: Discussionsupporting
confidence: 91%
“…E. coli strain LDH19 carrying bla CTX-M-132 was obtained from a urine sample from a female patient at a community hospital in Guangzhou, China. Clinical E. coli strains carrying bla CTX-M-14 and bla CTX-M-15 described in our previous study were also used in this study (10,11). The bla CTX-M genes were amplified by PCR using primers listed in Table 1 and cloned into the pET28b vector (Novagen).…”
Section: Methodsmentioning
confidence: 99%
“…However, antimicrobial-resistant K . pneumoniae strains have been isolated from marketed fresh vegetables [ 8 ], shrimp in international trade [ 9 ], and farm-raised chicken [ 10 ]. A recent report showed that foodborne K .…”
Section: Introductionmentioning
confidence: 99%